An Analysis of the Effects of Homegrown School Feeding Programme on Primary School Enrolment in Kaduna State - Suleman Ahmed Wan; SUmar Muhammad Salisu; Salihu Liman Wan; Fatima Muhammad Dambam (Balai Publikasi Indonesia, 2026)
This study evaluates the impact of the National Home-Grown School Feeding Programme (NHGSFP) on primary school enrolment in Sabon Gari LGA, Kaduna State, Nigeria, using Human Capital Theory and Maslow’s Hierarchy of Needs as theoretical frameworks. Through a descriptive survey design, mixed methods data were collected from 150 respondents, including pupils, parents, teachers, and administrators across three public primary schools, using questionnaires and interviews analyzed with SPSS and thematic methods. Results indicate a 45.45% enrolment increase from 1.1 million to 1.6 million pupils between 2015 and 2022, with 81.48% of respondents observing higher enrolment and 77.78% noting the programme’s influence on parental decisions, particularly benefiting low-income families and girls (42.96% increased female enrolment). Despite its effectiveness, with 77.77% rating it highly and 88.89% supporting its continuation, challenges like irregular meal supply (44.44%) and poor food quality (22.22%) negatively impact attendance for 55.55% of respondents. The study concludes that the NHGSFP significantly enhances educational access by addressing nutritional and economic barriers but requires logistical and funding reforms to sustain gains. Recommendations include improving supply chain logistics, enhancing meal quality and variety, stabilizing funding, strengthening monitoring systems, and increasing community involvement to ensure long-term educational benefits.